"Cost factors influencing in sending workers abroad", investigation on XYRATEX (Malaysia) Sdn. Bhd. / Shah Rizan Sariff - Sariff, Shah Rizan (Faculty of Business and Management, 2006)
XYRATEX is a leading provider of enterprise class data storage subsystems and network technology. As an equipment provider, moving the employee around the globe for product installation is the most crucial process in the manufacturing pipeline. The product delivery commitment date is tight up with the installation group travel arrangement Ideally the product and the people should arrive at the location on the same time. This activity has become very subjective to the certain XYRATEX customer countries that will lead to the increasing in costs towards the workers of XYRATEX who have been doing an overseas assignment in recent years especially after the September 11 event and during the SARS outbreak. Base on this reason, this research had been done to study "the cost factors influencing in sending workers abroad", investigation on XYRATEX (MALAYSIA) SON. BHO. hopefully, the findings of this research can give some benefits to the company. The objective of this research study is to analyze the significant of relationship between the logistic, accommodations, and administration cost toward the number of workers sending abroad. This write up will elaborate the costs that impacts to XYRATEX workers who had been sent to support their customers in various countries towards the globalization issues, which lead to the increasing in the costs in sending workers abroad that organization should consider. This study will provide and contribute to existing literatures; and it is also will provide some useful information and better understanding about formulating the human resources strategies that are cost effective, comply with the regulas and meet the customer expectation in a long run. Hopefully, the findings of this research can give some benefits to the company.